2019
DOI: 10.1038/s41467-019-12764-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and evolutionary analysis of human-expanded cognitive networks

Abstract: Cognitive brain networks such as the default-mode network (DMN), frontoparietal network, and salience network, are key functional networks of the human brain. Here we show that the rapid evolutionary cortical expansion of cognitive networks in the human brain, and most pronounced the DMN, runs parallel with high expression of human-accelerated genes (HAR genes). Using comparative transcriptomics analysis, we present that HAR genes are differentially more expressed in higher-order cognitive networks in humans c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
220
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(240 citation statements)
references
References 71 publications
20
220
0
Order By: Relevance
“…The specific wiring-rule names are shown along the horizontal-axis, with formal definitions provided in Table 2. show elevated expression in multimodal association networks (62).…”
Section: Discussionmentioning
confidence: 99%
“…The specific wiring-rule names are shown along the horizontal-axis, with formal definitions provided in Table 2. show elevated expression in multimodal association networks (62).…”
Section: Discussionmentioning
confidence: 99%
“…By systematically studying inter-nodal distances within the structural manifold, it may be possible to gain a more complete understanding of the difference between specialised systems at the periphery and more centrally localised zones of multimodal integration, such as the temporo-parietal junction and cingulate cortex. Many of these regions have undergone recent evolutionary expansion 65 , are sites of increased macaque-human genetic mutation rates 66 , and exhibit the lowest macaque-human functional homology 67 . In this context, the more complete model of cortical wiring provided by our structural manifold may play a critical role in advancing our understanding of how changes in cortical organisation have given rise to some of the most sophisticated features of human cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encompassed in both genomic regions were organized following highly similar co-expression patterns which may provide clues to FC-similarities between CNVs. Recent work has shown that the brain transcriptome is following broad spatial trends that are closely related to the functional network architecture 36, 37 .…”
Section: Discussionmentioning
confidence: 99%